THE ROLE OF RESIDUAL 2:1 PHYLLOSILICATES IN LATERITIC METALLOGENESIS: Ni AND Cu DEPOSITS IN SERRA DOS CARAJÁS, BRAZILIAN AMAZÔNIA - Oliveira, S. M. Barros de; Silva, M. L. M. de Carvalho e; Toledo, M. C. M. de (Geochimica Brasiliensis, 2011)